2001
DOI: 10.1080/02699050110045161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pocket-computer memory aids for people with brain injury

Abstract: Two styles of pocket computer memory aid were compared as support for people who had sustained non-progressive, closed-head brain injury. A purpose-designed interface provided a diary with auditory alarms, a notebook and links between diary entries and specific notepages. One computer had a physical keyboard, the other did not. Twelve adult volunteers were loaned each computer for 2 months, with a 1 month gap between, in counterbalanced order. It was found that all participants could use the memory aids, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 4 publications
(4 reference statements)
1
42
0
Order By: Relevance
“…Facilitators reported that the morning reminder was a minimal intervention compared to their typical pattern of providing students with prompts throughout the day related to their schedules. Results from this study are similar to the success in small-scale adult studies of handheld organizers (Kim et al, 1999(Kim et al, , 2000Kirsch et al, 2004;Wright et al, 2001). They all suggested that handheld organizers enhanced the ability of patients to complete suggested tasks with less direct intervention from those around them.…”
Section: Discussionsupporting
confidence: 88%
“…Facilitators reported that the morning reminder was a minimal intervention compared to their typical pattern of providing students with prompts throughout the day related to their schedules. Results from this study are similar to the success in small-scale adult studies of handheld organizers (Kim et al, 1999(Kim et al, , 2000Kirsch et al, 2004;Wright et al, 2001). They all suggested that handheld organizers enhanced the ability of patients to complete suggested tasks with less direct intervention from those around them.…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-four usability trials did not contribute evidence on treatment effect as no experimental data was reported. Finally, two included studies (Sohlberg, Fickas, Hung, & Fortier, 2007;Wright et al, 2001), despite trialing ATC with a clinical population, did not address treatment effect.…”
Section: Resultsmentioning
confidence: 99%
“…Although the ease of use of such software applications varies across the range of devices available and the platform on which they run (PalmOS/PocketPC/EPOC), they are not designed for memory-impaired people. Wright et al [62] conducted a study in which an interface specifically designed for brain-injured users was employed on two styles of PDAs. It was found that users who had suffered traumatic brain injury could use the PDAs successfully as memory aids, pointing to the need for a custom-designed interface for such users.…”
Section: Current Electronic Memory Aids and Usabilitymentioning
confidence: 99%